Sejarah Peradaban Islam Sebagai Ilmu Pengetahuan - Tarigan, Mardinal; Mauluddin Sitorus, Ahmad Ardhi; Amelia, Lydia (Indo-MathEdu Intellectuals Journal, 2023)
History encompasses the journey of human life in shaping the development of the world throughout time. Each history holds meaning and value, allowing humans to create their own history, and history, in turn, shapes humanity. Using history as a living material generates various analyses in the cultural atmosphere of that historical period. History repeats itself, bringing back old and similar events. History holds significance and provides meaning, wherein humans are like a world spinning around themselves. This research is a literature review or library research with a literature review of books, journals, and notes. The researcher solely relies on literary sources, engaging in activities such as reading, note-taking, and processing research materials. The result of this research is about the history of Islamic civilization as a field of knowledge. Knowledge rapidly flourished during the Abbasid Caliphate. This knowledge is divided into two categories: naqli (textual) and aqli (rational) sciences